Heparin and Related Drugs: Beyond Anticoagulant Activity. (30th July 2013) - Page, Clive
Abstract : Heparin has been widely used as an anticoagulant for more than 80 years. However, there is now considerable evidence that heparin also possesses anti-inflammatory activity, both experimentally and clinically. Importantly in many instances, the anti-inflammatory actions of heparin are independent of anticoagulant activity raising the possibility of developing novel drugs based on heparin that retain the anti-inflammatory activity. Heparin exhibits anti-inflammatory activities via a variety of mechanisms including neutralization of cationic mediators, inhibition of adhesion molecules, and the inhibition of heparanase, all involved in leukocyte recruitment into tissues. It is anticipated that furthering our understanding of the anti-inflammatory actions of heparin will lead to the development of novel anti-inflammatory drugs for a variety of clinical indications.